Quality of Pinus sp. pellets with kraft lignin and starch addition - Castro, Paula Gabriella Surdi (2021)
Pellets are widely used for power generation because they use renewable raw material with easy storage, transport and high energy density. However, the structural fragility, disintegrating during handling, transport and storage, is one of the main problems of pellets, but the addition of binders/ additives can minimize this fragility. The objective of this study was to evaluate the properties of wood pellets with the addition of starch (corn and wheat) and kraft lignin in different proportions. Pellets were produced with the addition of starch (wheat and corn) and kraft lignin in the proportions of 1, 2, 3, 4 and 5% in relation to the mass of wood particles of Pinus sp., with 12% moisture (dry basis), classified in 3 and 1 mm sieves and compacted in a pelleting press in the laboratory, according to European standard EN 14961-2. Physical and mechanical properties of the pellets were evaluated and their densitometric profiles obtained from the Faxitron LX-60 X-ray equipment. Corn starch and kraft lignin additives at 4% improved pellet properties (density, fines and hardness), reducing their losses during handling, storage and transport